Promoting participation and engagement: Ireland’s experiences across three decades of international large-scale assessments - Delaney, Emer; Clerkin, Aidan; Karakolidis, Anastasios; Gilleece, Lorraine; Millar, David (Frontiers in Education, 2025)
In large-scale assessments, the collection of high-quality representative data depends in part on (i) securing high participation rates and (ii) ensuring that participants demonstrate a sufficient level of engagement. This article explores the challenges of promoting participation and engagement with reference to Ireland’s experiences throughout multiple cycles of international and national large-scale assessments. Some factors likely to have influenced participation and/or engagement in the Irish context include: (i) the rising profile of large-scale assessments due to their prominence within a national strategy to improve literacy and numeracy; (ii) the transition of studies from paper-based to digital administration; (iii) the publication of new data protection legislation (both European and national); and (iv) pressures resulting from the COVID-19 pandemic. Initiatives implemented by Ireland’s national study centre with the aim of promoting participation in and engagement with large-scale assessments can be broadly classified as relating to consultation, promotion, and support. Lessons from Ireland’s experiences are discussed in relation to future avenues of investigation that may increase our understanding of facilitators and barriers to engagement. Ireland’s experiences offer valuable lessons that could inform practices in other countries.